2016
DOI: 10.1063/1.4954966
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced copper micro/nano-particle mixed paste sintered at low temperature for 3D interconnects

Abstract: An enhanced copper paste, formulated by copper micro-and nano-particles mixture, is reported to prevent paste cracking and obtain an improved packing density. The particle mixture of two different sizes enables reduction in porosity of the micro-paste and resolves the cracking issue in the nanopaste. In-situ temperature and resistance measurements indicate that the mixed paste has a lower densification temperature. Electrical study also shows a $12Â lower sheet resistance of 0.27 X/sq. In addition, scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In fact, such crack propagation was observed for the Cu films prepared from AEP–Cu NPs and AB–Cu NPs after the environmental stability experiments. In contrast, the mixing of micrometer‐sized Cu particles with nanometer‐sized Cu NPs in the composite ink could prevent the sintered Cu film from cracking and improved the packing density . As a result, the sintered Cu film from the composite ink showed high stability even after storage in the humid environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, such crack propagation was observed for the Cu films prepared from AEP–Cu NPs and AB–Cu NPs after the environmental stability experiments. In contrast, the mixing of micrometer‐sized Cu particles with nanometer‐sized Cu NPs in the composite ink could prevent the sintered Cu film from cracking and improved the packing density . As a result, the sintered Cu film from the composite ink showed high stability even after storage in the humid environment.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, besides low‐temperature sintering of Cu‐based inks, ensuring the durability of sintered Cu films to safeguard their environmental stability and mechanical flexibility has become the most important task from a practical standpoint . The mechanical properties of sintered Cu films on flexible substrates are an important factor of their practical application to flexible devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influences of the ink solvent, the solid fraction of the ink, the drying treatment, and the sintering parameters affect the crack formation. Dai et al reported a mixed paste of Cu micro- and nanoparticles to prevent cracking and achieved an improved packing density [ 123 ]. The particle mixture of two different sizes reduced the porosity of the micro-paste and resolved the cracking issue in the nano-paste.…”
Section: Formulation Designs In Cu-based Mixed Inks/pastesmentioning
confidence: 99%
“…Current additive manufacturing technologies, such as inkjet printing, microextrusion, and powder bed fusion are hardly optimized for high‐resolution (smaller than 30 µm) printing of common metals with a high melting point such as copper, gold, and platinum. Therefore, metal nanoparticle inks and pastes have been used for manufacturing of functional and flexible devices in complex shapes. However, the geometry and properties of printed objects are constrained by the liquid wetting or porosity caused by the postprinting thermal sintering step.…”
mentioning
confidence: 99%